Managing School Administrators’ Effectiveness Through Capacity Building Programmes in Secondary Schools of Sokoto State, Nigeria - Muhammad, S. Mera; Bolatito, A. Omotayo (Kashere Journal of Education, 2022)
The study examined the management of school administrators’ effectiveness through capacity building training and development in secondary schools in Sokoto state, Nigeria. The study used descriptive survey research design and the population of the study consisted of 161 participants (school administrators). Research Advisor (2006) was used to select sample size of 132, using multi-stage sampling techniques such as deliberate, proportionate and simple random sampling. Self-constructed questionnaire titled: Managing school Administrators. Effectiveness through Capacity Building Questionnaire (MSAETCBQ) to collect data based on four (4) Likert scale rating. Face and content validity of the research instrument was done by jury experts in educational administration and planning, Usmanu Danfodiyo University, Sokoto, Nigeria. The study used test re-test method of reliability for the research instrument through a pilot study conducted and a reliability index of 0.82 was obtained. Descriptive statistics such as mean (X), percentages (%), tables and frequency counts were used for the data analysis. The study found that school administrators’ regular participation in capacity building programmes updates and enhances their administrative effectiveness. The study recommended that, there is need for government through the Ministry of education to provide adequate funds for regular capacity building programmes for school administrators for improved skills and effective service delivery.